2012
DOI: 10.1038/onc.2011.621
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs and cancer: a new frontier of translational research?

Abstract: Tiling array and novel sequencing technologies have made available the transcription profile of the entire human genome. However, the extent of transcription and the function of genetic elements that occur outside of protein-coding genes, particularly those involved in disease, are still a matter of debate. In this review, we focus on long non-coding RNAs (lncRNAs) that are involved in cancer. We define lncRNAs and present a cancer-oriented list of lncRNAs, list some tools (for example, public databases) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
735
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 920 publications
(756 citation statements)
references
References 181 publications
0
735
0
10
Order By: Relevance
“…Furthermore, there currently exists no approved targeted therapy for TNBC (lacks estrogen receptor, progesterone receptor and HER2 amplification), which frequently exhibits highly malignant behaviour and resistance to conventional chemotherapies [27]. The identification of novel therapeutic targets for multiple breast cancer subtypes is therefore important, and lncRNAs may offer new opportunities in this regard, given their emerging roles as regulators of fundamental biological processes [1][2][3][4][5]. Indeed, GAS5 is already of particular interest in relation to breast cancer, since its expression is down-regulated in tumour tissue [9], and patient prognosis is significantly related to GAS5 transcript levels [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there currently exists no approved targeted therapy for TNBC (lacks estrogen receptor, progesterone receptor and HER2 amplification), which frequently exhibits highly malignant behaviour and resistance to conventional chemotherapies [27]. The identification of novel therapeutic targets for multiple breast cancer subtypes is therefore important, and lncRNAs may offer new opportunities in this regard, given their emerging roles as regulators of fundamental biological processes [1][2][3][4][5]. Indeed, GAS5 is already of particular interest in relation to breast cancer, since its expression is down-regulated in tumour tissue [9], and patient prognosis is significantly related to GAS5 transcript levels [10].…”
Section: Discussionmentioning
confidence: 99%
“…Long ncRNAs (size range: 0.2 -100 kb) are emerging as key regulators of fundamental cellular processes and are increasingly recognized as of importance in the pathogenesis, diagnosis and treatment of major cancers, including breast cancer [1][2][3][4][5]. Apart from ribosomal RNAs, lncRNAs comprise a plethora of mRNA-like transcripts (long intergenic ncRNAs, pseudogene-derived transcripts and sequences that are intronic or antisense to protein coding genes) [1,6,7], which can act as signals, scaffolds, guides, decoys or tethers to modulate, for example, the maintenance of subcellular structures, chromatin modification and transcriptional/post-transcriptional regulation of gene expression [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…These factors include the tremendous complexity and diversity of the lncRNA landscape, the finding that lncRNAs are often located at crucial sites (eg, regions of singlenucleotide polymorphisms (SNPs), amplifications, or at common breakpoints), the presence of sequence motifs and other elements that result in specific structures, their regulation, and their functional relationships with other nucleic acids and proteins. 11,16 In fact, previous studies have shown that particular deregulated lncRNAs are important regulators of tumor formation and progression. 17,24 For example, the antisense intergenic RNA HOX Antisense Intergenic RNA (HOTAIR) is highly expressed in multiple types of primary somatic tumors, such as hepatocellular carcinoma, 25,26 pancreatic cancer, 27 and gastric cancer, 28 as well as some metastatic tumors, including metastatic breast tumors 29 and melanoma.…”
Section: Lncrnas In Cancermentioning
confidence: 99%
“…10 And moreover, a significant proportion of lncRNAs may possess coding and non-coding activities. 11 Combining with these characters, Mercer et al 2 proposed a definition that describes lncRNAs as 'RNA molecules that may function as either primary or spliced transcripts and do not fit into known classes of small RNAs or into classes of structural RNAs'. This undated definition overcomes the restriction of ORF and length that was arbitrarily set.…”
mentioning
confidence: 99%
See 1 more Smart Citation